Storm-Surge Flooding on the Yukon-Kuskokwim Delta, Alaska - Terenzi, John; Jorgenson, M. Torre; Ely, Craig R. (ARCTIC, 2014)
Coastal regions of Alaska are regularly affected by intense storms of ocean origin, the frequency and intensity of which are expected to increase as a result of global climate change. The Yukon-Kuskokwim Delta (YKD), situated in western Alaska on the eastern edge of the Bering Sea, is one of the largest deltaic systems in North America. Its low relief makes it especially susceptible to storm-driven flood tides and increases in sea level. Little information exists on the extent of flooding caused by storm surges in western Alaska and its effects on salinization, shoreline erosion, permafrost thaw, vegetation, wildlife, and the subsistence-based economy. In this paper, we summarize storm flooding events in the Bering Sea region of western Alaska during 1913 – 2011 and map both the extent of inland flooding caused by autumn storms on the central YKD, using Radarsat-1 and MODIS satellite imagery, and the drift lines, using high-resolution IKONOS satellite imagery and field surveys. The largest storm surges occurred in autumn and were associated with high tides and strong (> 65 km hr-1) southwest winds. Maximum inland extent of flooding from storm surges was 30.3 km in 2005, 27.4 km in 2006, and 32.3 km in 2011, with total flood area covering 47.1%, 32.5%, and 39.4% of the 6730 km2 study area, respectively. Peak stages for the 2005 and 2011 storms were 3.1 m and 3.3 m above mean sea level, respectively—almost as high as the 3.5 m amsl elevation estimated for the largest storm observed (in November 1974). Several historically abandoned village sites lie within the area of inundation of the largest flood events. With projected sea level rise, large storms are expected to become more frequent and cover larger areas, with deleterious effects on freshwater ponds, non-saline habitats, permafrost, and landscapes used by nesting birds and local people. Les régions côtières de l’Alaska sont souvent touchées par d’intenses tempêtes d’origine océanique. La fréquence et l’intensité de ces tempêtes devraient augmenter en ...